Effect of Complex Ion Beam/Plasma Treatment of the Surface Functionalization and Crystal Phase Transition of Piezoelectric Poly(vinylidene fluoride) - Lee, Ji Seok; Kim, Gwang Ho; Hong, Soon Man (TAYLOR & FRANCIS LTD, 2008)
We scrutinized the effect of complex ion beam and plasma treatment on the surface functionalization and crystal phase change of poly(vinylidene fluoride) films. The stretched and poled PVDF films were used for this investigation. Ion-beam and plasma treatment were employed for the surface modification of PVDF. The surface treatments induced some changes of chemical composition as well as changed the morphology of PVDF surface. It had a large influence on the interfacial adhesion with thermally deposited metal electrodes on the PVDF. Surface modifications such as ion beam irradiation and plasma treatment played a pivotal role in the determination of interfacial strength between PVDF and electrodes as well as the change of crystal structure in electromechanical PVDF film. While the amount of beta-phase crystal in PVDF decreased with treatment time, the interfacial adhesion increased with the modification time. In this research, we were able to find optimum treatment conditions for enhancing the adhesion and retaining piezoelectric structure.
Keywords: ADHESION; FILMS